A Teacher-Based Checklist for the Assessment of Student Learning and Development - David William Oborne EdD.; Ying Cheng Hoh PhD.; Lynda Ruth Hutchinson PhD (International Journal of Education Policy and Leadership, 2014)
This paper reports on two studies that evaluated the statistical validity of the Classroom Learning and Development Questionnaire as a universal screening and early identification observation instrument within the North American context. The Classroom Learning and De-velopment Questionnaire was first proposed and tested in Hong Kong in the mid-1990s. It has been used as an integral part of the school procedures in the Hong Kong school system since it was first launched and has spawned a number of intervention programs for students within the Hong Kong Educational Authority. The Classroom Learning and Development Questionnaire (CLDQ) has been adapted from the Hong Kong study as a Tier I observation instrument to be used in the North American context. Results of the principal component analysis (PCA) in Study 1 (N = 820) extracted six components, which exhibited adequate to high levels of internal consistency. Results of Study 2 (N = 117) indicated statistically significant and negative relationships between the CLDQ subscales and Teacher Rating Form (TRF) (Achenbach, 1991) variables, demonstrating evidence of convergent validity. Based on the findings of these studies, the authors conclude that the screening protocol does present as a robust instrument capable of supporting screening at a primary prevention level. Based on this study, it is argued that classroom teachers hold a wealth of information concerning each student and that this, when presented in a systematic fashion, leads to greater understanding of individual and group learning needs and may lead to pre-emptive actions which would benefit students’ learning trajectories.